THE INFLUENCE OF CONSUMER PERCEPTION ON PURCHASE INTENTION OF USING INDIHOME PRODUCT IN MANADO CITY - Kahimpong, Incha Restafanti; Tielung, Maria V. J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
The existence of this Triple Play Services or Telkom’s Fiber To The Home (FTTH) service which known by the trademark IndiHome has successfully attracted the public interest to use IndiHome, especially in Manado City. The way the customer uses this product will have an impact on interest in purchasing the IndiHome. This research is aimed to analyze the influence of customer perception of value, price and quality on customer purchase intention of using IndiHome. The data obtained from the sample of 110 respondents of IndiHome users in Manado City were analyzed with quantitative analysis by using questionnaires and Multiple Regression Analysis. The sample technique is Random Sampling, in order to get results quickly and efficiently obtain the information needed in this research. Result and conclusion show perceived value, perceived price and perceived quality have positive and significant influence on customer purchase intention simultaneously and partially. To marketing company, researcher to keep enhancing and maintain the product’s quality and value, also should be more consider about the price management. Keywords: customer perception, customer purchase intention